PERANCANGAN SISTEM DAN DESAIN APLIKASI YEZ TRAVEL BERBASIS WEB - Garneto Alvan; Bagus Mulyawan; Manatap Dolok Lauro (Fakultas Teknologi Informasi Universitas Tarumanagara, 2025)
Indonesia is a country rich in cultural diversity, and each region in Indonesia offers its own unique characteristics. This is also the case with West Kalimantan. The natural beauty presented by West Kalimantan has the potential to attract many local and international visitors. More than that, the current influence of globalization certainly has an impact on the development of tourism. One of the promising businesses in this field is the travel industry. To support Yez Travel in the travel business, it is important to digitalize the services. The main goal is to ensure the sustainability of Yez Travel's business. This research will design a web-based application that provides tour packages and car rentals. The web is designed using HTML and CSS programming languages. The framework used is Laravel and Bootstrap and MySQL as the database. The method used to design the Yez Travel web is the Agile Scrum method. With this web, Yez Travel customers can more easily make transactions.